Vaccination Lottery - Duk Gyoo Kim (Center for Economic Studies and ifo Institute (CESifo), 2021)
Ohio announced a Vax-a-Million Lottery in May 2021 to encourage people vaccinated. If people may avoid vaccination because (1) they worry about rare but critical side effects or (2) they want to free ride on herd immunity, the vaccination lottery may work better or worse than a lump-sum transfer to the contributors for herd immunity. I experimentally compare the effectiveness of the vaccination lottery over a lump-sum transfer. Overall, vaccination lottery works better, and it particularly incentivizes probability-weighting subjects.
Keywords: 330; vaccination incentives; lottery; Covid-19; laboratory experiments